Myristoylation-dependent replication and assembly of human immunodeficiency virus 1. - Bryant, M (1990)
Covalent linkage of myristic acid to the N-terminal glycine residue of Pr55gag, the precursor of the major structural proteins of human immunodeficiency virus 1 (HIV-1), facilitates an essential step in virus assembly and propagation. Substitution of the myristoyl-acceptor glycine with alanine, in a functional clone of HIV-1, eliminates virus replication. Complementation of this defect, in trans, restores infectious particle production. The nonmyristoylated (myr-) gag precursor accumulates in infected cells and is not processed into the mature capsid components of the intact virion. However, myr- Pr55gag can be processed by purified HIV protease in vitro, demonstrating that the myristoyl moiety is not required for cleavage by the protease. Myristoylation of Pr55gag is not necessary for localization but is required for stable membrane association and assembly of HIV-1.